Pengaruh Kemampuan dan Sikap Terhadap Kinerja Pegawai Pada Dinas Pendidikan dan Kebudayaan Kabupaten Padang Lawas - Romatua Nasution; Tanjung , Ali Mukti; Musri, Ali (Asosiasi Ide Bahasa Kepri, 2024)
The aim of this research, in essence, is to find out how significant the influence of Ability and Attitude is on Employee Performance. The method used is the analytical descriptive method with a quantitative approach. The population in this study was 31 people and the sample was 30 people and the sampling technique was purposive sampling. Data collection techniques using questionnaires, documentation, interviews and literature studies. The data analysis technique uses multiple linear regression. The results of the research show that ability has a significant influence of 0.530 or 53.0% on the performance of employees of the Department of Education and Culture of Padan Lawas Regency, the influence is in the medium category. Where the skills are better, employee performance will also be higher. Attitude has a significant influence of 0.589 or 58.9% on the performance of employees of the Education and Culture Department of Padan Lawas Regency, the influence is in the medium category. There is a positive influence where the better the attitude, the higher the employee's performance. Simultaneously, the ability and attitude variables have a significant influence of 0.509 or 50.9% on the performance of employees of the Padan Lawas Regency Education and Culture Department in the moderate category, with the remaining 20.6% explained by other factors.